Determining 1D velocity model from local earthquake data in the South Hangay region, central Mongolia - Dashdondog, Mungunsuren; Chimed, Odonbaatar; Meltzer, Anne; Erdenetsogt, Nomin-Erdene; Stachnik, Josh (Proceedings of the Mongolian Academy of Sciences, 2020)
One dimensional (1D) velocity models are still widely used for computing earthquake locations at seismological centers. The location accuracy of an earthquake strongly depends on the velocity model used to compute the location. In the past, the local velocity model developed for the Hangay region was lacking precision due to insufficient data. Within the framework of the “Intracontinental Deformation and Surface Uplift- Geodynamic Evolution of the Hangay Dome, Mongolia, Central Asia” project [15], 72 seismic Broadband stations network were deployed in the Hangay Dome. This gives us an opportunity to estimate the crustal velocity structure of the South Hangay region using recorded local earthquake data. For this purpose, available velocity models for the South Hangay region have been re-evaluated. By simultaneous invertion P- and S-wave arrival times using VELEST algorithm, we estimated minimum 1D velocity models, station corrections, hypocentre locations, and origin times for the south Hangay region. Consequently, 1D crustal velocity model is proposed for the South Hangay region. This new model is expected to improve the accuracy of the routine hypocenter determination and as initial reference models for seismic tomography study.